2008
DOI: 10.1002/app.27960
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of polystyrene in supercritical methanol

Abstract: The degradation of polystyrene (PS) in supercritical methanol was carried out under reaction temperatures ranging from 340 to 4208C and pressures of 10-30 MPa. The selectivity of liquid products was investigated at various reaction conditions. As the reaction proceeded, the selectivity of styrene monomer, dimer, 1,3-diphenyl propane, and 1,3-diphenyl butane had a declining tendency, whereas that of the rest (i.e., toluene, ethyl benzene, isopropyl benzene, and 3-phenyl propanol, etc.) had an inclining tendency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Shin et al carried out pyrolysis of PS employing water, n-hexane and methanol under supercritical settings and found that the process utilizing water as a solvent showed the greatest activation energy of 157 kJ/mol, while the process employing n-hexane and methanol reported activation energy of 132 kJ/mole and 117.2 kJ/mole, respectively [ 92 ]. This suggests that organic solvents have higher efficiency than water.…”
Section: Process Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Shin et al carried out pyrolysis of PS employing water, n-hexane and methanol under supercritical settings and found that the process utilizing water as a solvent showed the greatest activation energy of 157 kJ/mol, while the process employing n-hexane and methanol reported activation energy of 132 kJ/mole and 117.2 kJ/mole, respectively [ 92 ]. This suggests that organic solvents have higher efficiency than water.…”
Section: Process Parametersmentioning
confidence: 99%
“…Some scientific studies of pyrolysis of PS employing various solvents explored the influence of reaction time on the yield of oil [ 92 , 93 ]. The studies showed that prolonging the time of reaction increased production of oil.…”
Section: Process Parametersmentioning
confidence: 99%
“…4a). 49,50 The surface curvature and distribution of protrusions for both the functionalised PET surfaces are relatively different. 51 The CPET surface possesses a regular curvature and uniform distribution of peak to valley topography with isolated growth of micro-and nano-grooves (Fig.…”
Section: Characterisation Of Pet Textilesmentioning
confidence: 99%
“…The amplitude and the number of these spikes increase with the increase in applied voltage. These spikes were connected to the development of micro discharges of tens of nanosecond interval in the gap space [24].…”
Section: Electrical Parameters Of Gdbd Reactor Characteristicsmentioning
confidence: 98%